1998
DOI: 10.1136/hrt.79.3.256
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the effectiveness of long term beta  blocker treatment for dilated cardiomyopathy by signal averaged electrocardiography

Abstract: AbstractsObjective-To determine whether the effectiveness of long term blocker treatment for idiopathic dilated cardiomyopathy can be predicted by signal averaged electrocardiography (ECG). Patients-31 patients with dilated cardiomyopathy and without bundle branch block were included in a retrospective study and 16 in a prospective study. Signal averaged ECG criteria for good response were defined as two or more of the following: QRS duration < 130 ms, RMS40 > 20 µV, LAS40 < 40 ms (sensitivity 81%, specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Yamada et al found that intercellular fibrosis on myocardial biopsy predicted a poor response to metoprolol therapy. Moreover, they reported that such fibrosis could be estimated by means of signal averaging, and suggested this noninvasive method could predict clinical response to metoprolol therapy with a sensitivity of 85% and a specificity of 91% [38][39][40]. Similarly, Suwa et al demonstrated that myocardial integrated ultrasonic backscatter imaging, useful in delineating myocardial fibrosis, could help predict response to therapy with bisoprolol [41].…”
Section: Predictors Of Clinical Responsementioning
confidence: 97%
“…Yamada et al found that intercellular fibrosis on myocardial biopsy predicted a poor response to metoprolol therapy. Moreover, they reported that such fibrosis could be estimated by means of signal averaging, and suggested this noninvasive method could predict clinical response to metoprolol therapy with a sensitivity of 85% and a specificity of 91% [38][39][40]. Similarly, Suwa et al demonstrated that myocardial integrated ultrasonic backscatter imaging, useful in delineating myocardial fibrosis, could help predict response to therapy with bisoprolol [41].…”
Section: Predictors Of Clinical Responsementioning
confidence: 97%